Validation of Regional Lymph Node Excisional Biopsy for Staging Oral and Maxillofacial Malignant Neoplasms in 97 Dogs and 10 Cats (2006-2016). (June 2019) - Odenweller, Patrick H.; Smith, Mark M.; Taney, Kendall G.
The objective of this retrospective clinical study was to confirm the validity of excisional biopsy of regional lymphocentrums for staging oral and maxillofacial neoplasms in a population of 97 dogs and 10 cats. Patients diagnosed with oral and maxillofacial malignant neoplasms underwent ipsilateral excisional biopsy of the mandibular, parotid, and medial retropharyngeal lymphocentrums that receive afferent drainage from the oral and maxillofacial region followed by curative intent surgery of the neoplasm. Biopsy specimens and the resected neoplasm were submitted to a commercial pathology laboratory for histopathologic assessment. The incidence of metastasis to one or more regional lymphocentrums was 14.0%. Of the cases with metastatic disease, 26.7% did not involve the mandibular lymphocentrum. Although the incidence of regional lymph node metastasis was less than reported previously, regional lymph node assessment is warranted in cases of oral and maxillofacial neoplasia.